Book review: Por uma Geografia dos espaços vividos [For a geography of lived spaces], by Angelo Serpa - CLAUDIO (Geografares, 2020)
The book “Por uma Geografia dos espaços vividos”, structured in eight chapters, brings together reflections and experiences, articulated over the last few years, in classes and research at the Department of Geography of the Universidade Federal da Bahia [Federal University of Bahia] (UFBA), an institution in which the author works as a professor and researcher since 1996.